Implication of The Strict Liability Principle in Immigration Criminal Cases in Indonesia: Implikasi Prinsip Tanggung Jawab Mutlak Dalam Kasus Pidana Keimigrasian di Indonesia - Radhin, Azka Irtikha; Yuli, Yuliana (Rechtsidee, 2025)
General background: Immigration governance functions as a selective mechanism to safeguard national security amid increasing foreign arrivals and recurring administrative infractions. Specific background: Despite Indonesia’s commitment to the principle of geen straf zonder schuld, immigration law uniquely allows punishment based solely on the fulfillment of objective elements such as overstay, unlawful entry, or presence in prohibited areas. Knowledge gap: Although the strict liability principle is applied in court decisions, its legal basis remains implicit due to the absence of explicit statutory provisions detailing which immigration offenses fall under this doctrine. Aims: This research analyzes the application, legal foundations, and consequences of strict liability within immigration criminal proceedings. Results: Findings reveal significant inconsistencies between legislative norms and judicial practice, posing risks to legal certainty, fairness, and the protection of suspects’ procedural rights. Novelty: The study identifies critical normative gaps that permit broad administrative discretion and potential overcriminalization. Implications: Clearer statutory formulation and strengthened procedural safeguards are necessary to balance state security interests with substantive justice and human rights protections. Highlights: Strict liability in immigration law is applied implicitly, creating uncertainty in defining which offenses qualify. This principle conflicts with the fundamental doctrine of geen straf zonder schuld, potentially weakening suspect rights. Clearer statutory regulation is needed to prevent overreach and ensure proportional, just enforcement. Keywords: Strict Liability, Immigration Law, Legal Certainty, Mens Rea, Fair Trial